A review of recent progress in improving the fracture toughness of epoxy‐based composites using carbonaceous nanofillers - Mousavi, Seyed Rasoul; Estaji, Sara; Paydayesh, Azin; Arjmand, Mohammad; Jafari, Seyed Hassan; Nouranian, Sasan; Khonakdar, Hossein Ali (Polymer composites, 2022)
Epoxy resins (EPs) exhibit various extraordinary properties, including significant mechanical and thermal properties, low shrinkage, and high chemical resistance, opening a wide window of different applications such as adhesives, paints, coatings, etc. By contrast, EPs also have the undesirable behavior of being brittle and cannot sufficiently resist against the initiation and growth of cracks. Efforts are being made to enhance the toughening of EPs without sacrificing their other desirable properties. With the advent of nanotechnology, improving the toughening of EPs has gained momentum by incorporating different modified and unmodified nanofillers into these polymers. Since the discovery of carbonaceous nanofillers, especially carbon nanotubes (CNTs) and graphene (Gr), significant progress has been made in the development of EP‐based composites incorporating these nanofillers and their hybrids. The current review presents research progress during the last six years on the toughening of EPs using CNTs, Gr, and CNT‐Gr hybrids. Special attention is given to the chemical functionalization of these nanofillers, which has been demonstrated over and over again to significantly affect nanofiller dispersion in the EP matrix and subsequently its fracture properties. Details on the various toughening mechanisms of EP‐based composites are further provided. Toughening mechanisms in epoxy resins modified with carbon nanotubes and graphene